Comparative analysis of existing platforms for the development of vaccines against dangerous and extremely dangerous viral infections with pandemic potential - G. G. Onishchenko; T. E. Sizikova; V. N. Lebedev; S. V. Borisevich (Биопрепараты: Профилактика, диагностика, лечение, 2021)
The main triggers of new infectious diseases, including those with pandemic potential, are: spontaneous emergence of infectious strains which are more virulent for humans and contribute to transmission of pathogenic microorganisms, environmental changes, social and economic factors, increased contact rates between different regions. A successful pandemic response requires mass immunisation against a specific disease, aimed at the development of herd immunity which is based on the concept of indirect protection of the whole of the population by immunising a part of it. A well-grounded choice of the vaccine platform is central to dealing with this problem. The aim of the study was to compare characteristics of vaccine platforms (attenuated, inactivated, subunit, recombinant vector, DNA, and RNA vaccines) intended for mass immunisation against dangerous and extremely dangerous viral infections with pandemic potential. The study focused on the members of Poxviridae, Orthomyxoviridae and Coronaviridae families as potential pathogens. The vaccine platforms were compared in terms of the following parameters: capability of producing a robust immune response; protective efficacy; time required for vaccine development and testing; ability to produce vaccine in volumes required for mass immunisation; potential obstacles associated with the intended use of the vaccine. It is expected that in the next few decades DNA and RNA vaccine platforms will be most widely used for development of products against dangerous and extremely dangerous viral infections with pandemic potential, regardless of taxonomic groups of pathogens.